Acute sensorineural hearing loss in hemodialysis patients. (2nd July 2020) - Li, Tzu-Yu; Cheng, Po-Wen; Young, Yi-Ho
Abstract: Background: Approximately, 30–40% of patients experienced hearing loss under regular hemodialysis. Objective: This study reviewed our experience on treating acute hearing loss in patients under regular hemodialysis over the past two decades. Methods: Twenty-six patients having acute hearing loss under hemodialysis were divided into two groups based on their etiologies. Sixteen patients (16 ears) with sudden sensorineural hearing loss (SSHL) were assigned to Group A and 10 patients (13 ears) with endolymphatic hydrops (EH) were assigned to Group B. Results: No significant difference was noted between Groups A and B, regardless of hemodialysis duration, clinical manifestation, underlying systemic diseases, blood examination, and vestibular test battery. In contrast, serum osmolality was significantly lower in Group B (292 ± 11 mOsm/kg) than in Group A (310 ± 11 mOsm/kg). Furthermore, Group B (40 ± 14 dB) had better mean hearing level than Group A (87 ± 21 dB) in the initial audiogram, and a higher hearing improvement rate (69%) than Group A (19%). Conclusions and significance: Both SSHL and EH are major causes for precipitating acute hearing loss in hemodialysis patients. Compared to SSHL, the less deteriorated MHL and lower serum osmolality in EH provide two clues for differentiating acute hearing loss in hemodialysis patients.